1987
DOI: 10.3171/jns.1987.67.3.0456
|View full text |Cite
|
Sign up to set email alerts
|

Metameric capillary hemangioma producing complete myelographic block in an infant

Abstract: A variety of lesions of ectodermal, mesodermal, (rarely) endodermal, or mixed-cell layer origin involve the region of the conus medullaris. Some of these abnormalities produce cord tethering and others, such as lipoma, frequently present as masses. In the present case, an infant was discovered to have a lesion most closely resembling a capillary hemangioma involving the skin of the midline and right buttock, the deep soft tissues of the right buttock, the dura, and the conus medullaris. The origin of this cong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

1991
1991
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 3 publications
0
19
0
Order By: Relevance
“…The pathogenesis of this rare lesion remains unknown. Some theories of etiology 1,10,13,17 suggest that the origin may be from impaired movement and differentiation of primitive mesoderm from the embryonic mesodermal plate at the time when angioblastic differentiation begins (Days 21-24 of embryogenesis), hamartomatous proliferations of vascular endothelial cells, or congenital malformation following an autosomal dominant pattern of inheritance. Thus, various pathogenic mechanisms may cause intramedullary capillary hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pathogenesis of this rare lesion remains unknown. Some theories of etiology 1,10,13,17 suggest that the origin may be from impaired movement and differentiation of primitive mesoderm from the embryonic mesodermal plate at the time when angioblastic differentiation begins (Days 21-24 of embryogenesis), hamartomatous proliferations of vascular endothelial cells, or congenital malformation following an autosomal dominant pattern of inheritance. Thus, various pathogenic mechanisms may cause intramedullary capillary hemangiomas.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge only 14 cases have been previously described since the publication of the earliest report in 1987. 10 The optimal management for this lesion has not been fully determined. In this study, we retrospectively review and discuss the clinical, radiological, surgical, and pathological features of 5 patients with intramedullary capillary hemangiomas, the first case series from a single center.…”
Section: ©Aans 2013mentioning
confidence: 99%
“…There has been only 1 documented case of spinal capillary hemangioma occurring in an infant [12]. Mawk et al [12 ]reported a case of metameric capillary hemangioma producing complete myelographic block in a 7-month-old infant.…”
Section: Discussionmentioning
confidence: 99%
“…The occurrence of intradural extramedullary spinal capillary hemangiomas is relatively rare, with only 36 cases reported in the literature [4,5,6,7,8,9,10,11,12,13,14,15,16,17]. Most documented cases have been described on the spinal roots and cauda equina of adults [10,11,12,13,14,15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation